2004
DOI: 10.1038/sj.ejcn.1601993
|View full text |Cite
|
Sign up to set email alerts
|

New bioimpedance analysis system: improved phenotyping with whole-body analysis

Abstract: Objective: Bioimpedance analysis (BIA) is a potential field and clinical method for evaluating skeletal muscle mass (SM) and %fat. A new BIA system has 8-(two on each hand and foot) rather than 4-contact electrodes allowing for rapid 'whole-body' and regional body composition evaluation. Design: This study evaluated the 50 kHz BC-418 8-contact electrode and TBF-310 4-contact electrode foot-foot BIA systems (Tanita Corp., Tokyo, Japan). Subjects: There were 40 subject evaluations in males (n ¼ 20) and females (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
280
2
14

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 317 publications
(308 citation statements)
references
References 19 publications
(28 reference statements)
9
280
2
14
Order By: Relevance
“…The impedance scales used in this study has been validated against DXA in mixed populations of children and adults and found to be superior to previous BIA methods. 10 More recently a pediatric validation of the BC-418MA model against DXA and air-displacement plethysmography (BodPod) has been performed. 11 In samples of 45 boys (age 11.073.6 year) and 34 girls (age 11.073.0 year) results were highly correlated with DXA (r ¼ 0.91, SEE ¼ 4.46%) and mean values did not differ significantly.…”
Section: Anthropometric and Body Fat Measurementsmentioning
confidence: 99%
“…The impedance scales used in this study has been validated against DXA in mixed populations of children and adults and found to be superior to previous BIA methods. 10 More recently a pediatric validation of the BC-418MA model against DXA and air-displacement plethysmography (BodPod) has been performed. 11 In samples of 45 boys (age 11.073.6 year) and 34 girls (age 11.073.0 year) results were highly correlated with DXA (r ¼ 0.91, SEE ¼ 4.46%) and mean values did not differ significantly.…”
Section: Anthropometric and Body Fat Measurementsmentioning
confidence: 99%
“…Percent body fat measured using the Tanita BC-418 has been shown to correlate highly with the reference measure of dual-energy X-ray absorptiometry. 12 As impedance fluctuates with the distribution of body fluid, to improve accuracy, participants were required to urinate before the measurement of percentage body fat was taken. Measurements of weight, BMI and body fat were repeated at the end of the study.…”
Section: Measurements Of Body Weight and Compositionmentioning
confidence: 99%
“…Arms were held in the straight down position without touching their sides. As previously described (Pietrobelli et al, 2004), the SBIA system consists of four contact electrodes (two anterior and two posterior) that are mounted on the surface of a platform scale and each extremity handgrip has an anterior and posterior electrode. All measurements are carried out using a constant singlefrequency current (50 kHz, 500 mA).…”
Section: Segmental Bioelectrical Impedance Analysismentioning
confidence: 99%
“…These contact-electrode analyzers, which measure impedance as a participant stands on a scale-like platform, differ significantly from the traditional BIA method that requires the accurate placement of gel electrodes at specific anatomical locations. LBIA and SBIA have been found to have overall performance characteristics for impedance measurement and body composition analysis similar to traditional BIA while offering the advantage of increased speed and ease of measurement (Nunez et al, 1997;Pietrobelli et al, 2004).…”
Section: Introductionmentioning
confidence: 99%